Evidence for a tumor suppressor role for the large tumor suppressor genes LATS1 and LATS2 in human cancer. - Yu, T.; Bachman, J.; Lai, Z.C. (Genetics, 2013)
The role of Large tumor suppressor LATS/Warts in human cancer is not clearly understood. Here we show that hLATS1/2 cancer mutations affect their expression and kinase activity. hLATS1/2 mutants exhibit a decreased activity in inhibiting YAP and tissue growth. Therefore, hLATS1/2 alleles from human cancer can be loss-of-function mutations.